The effects of community policing on fear of crime and perceived safety: findings from a pilot project in Trinidad and Tobago - Maguire, Edward R. (Policing and society, 2019)
Using findings from a quasi-experiment, this study examines whether the implementation of community policing in Gonzales, a distressed Caribbean community, reduced fear of crime and increased perceptions of safety. We use a pre-post, comparison group design with two groups. Data are based on three waves of citizen surveys carried out in both groups. Our findings reveal that from wave 1 to wave 2, the treatment area experienced an increase in fear relative to the comparison area; the effect size was small and positive, but was not statistically significant. The change in perceived safety from wave 1 to 2 in the treatment area was trivial and non-significant. From wave 2 to 3, the treatment area experienced a significant positive increase in perceptions of safety relative to the comparison area. The treatment area also experienced a small reduction in fear relative to the comparison area, but the effect was not statistically significant. Overall, we conclude that the early stages of implementing community policing in Gonzales may have increased fear but had no effect on perceived safety. Later and more robust implementation was associated with a significant increase in perceived safety and possibly a small reduction in fear.